Biophilic Design Application in School Common Areas: Exploring the Potential to Alleviate Adolescent Depression - Ji-Yoon Kim; Sung-Jun Park (Buildings)
This study proposes design strategies for incorporating biophilic design into common areas in schools, with consideration of adolescents’ levels of depression. Types of common areas and relevant biophilic design attributes were identified through a comprehensive review of existing literature. Using Stable Diffusion, visual representations of school common areas featuring biophilic elements were generated, and adolescents’ preferences for these attributes were surveyed. The analysis revealed that Weather & View was the most preferred attribute across all types of common areas. Furthermore, adolescents experiencing depressive symptoms showed a higher overall preference for biophilic design elements compared to their non-depressed peers, with notable gender differences within the depressed group. Specifically, those with mild depressive symptoms exhibited generally high preferences, particularly for attributes such as Water, Shape & Form, Image, and Material. Distinct patterns of preference also emerged depending on the specific application characteristics of the design. This study contributes by proposing tailored design strategies for different types of school common areas that reflect adolescents’ emotional profiles. Future research should incorporate multidimensional approaches, including field studies and investigation of user preferences and psychological responses, to further validate and refine biophilic design applications in educational environments.